2006
DOI: 10.1021/ja057798c
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Class of Sugar-Binding Boronic Acids, Soluble and Capable of Complexing Glycosides in Neutral Water

Abstract: This study describes a new class of carbohydrate-binding boronic acids. ortho-Hydroxymethyl phenylboronic acid (boronophthalide) was shown to be superior to the well-established dialkylamino ("Wulff-type") analogues, and it is more soluble in aqueous solvents. The most significant finding in this work is the surprising ability of ortho-hydroxyalkyl arylboronic acids to complex model glycopyranosides under physiologically relevant conditions. These boronic acid units appear to complex hexopyranosides mainly usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
326
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(335 citation statements)
references
References 25 publications
4
326
0
5
Order By: Relevance
“…The Hall group has provided an important solution to this problem when they showed that benzoboroxoles can bind methyl hexopyranosides in water at pH 7.5. [37] For glucopyranosides, the only significant binding site is the C-4/C-6 diol as all vicinal diols in this system are of a trans relationship. In galactopyranosides, there is an additional possible binding site: the C-3/C-4 cis-diol ( Figure 7): While a significant amount of research has been dedicated to the study of boronatemonosaccharide interactions, very little has been invested in borinate-monosaccharide exchange.…”
Section: Boron-based Monosaccharide Receptorsmentioning
confidence: 95%
“…The Hall group has provided an important solution to this problem when they showed that benzoboroxoles can bind methyl hexopyranosides in water at pH 7.5. [37] For glucopyranosides, the only significant binding site is the C-4/C-6 diol as all vicinal diols in this system are of a trans relationship. In galactopyranosides, there is an additional possible binding site: the C-3/C-4 cis-diol ( Figure 7): While a significant amount of research has been dedicated to the study of boronatemonosaccharide interactions, very little has been invested in borinate-monosaccharide exchange.…”
Section: Boron-based Monosaccharide Receptorsmentioning
confidence: 95%
“…Given the importance of glucose monitoring for patients with diabetes and for other applications, a great amount of effort has been directed towards the development of boronic acid-containing sensors that can operate under physiological conditions for routine monitoring. [56,57] Alternative applications of these boronic acid glucose sensors involve glucose imaging, and the use of novel polymeric materials that can be used for the controlled release of insulin on binding of glucose. [37] Finally, fluorescent boronic acid sensors can be used in a diagnostic manner for the detection and labelling of fucosylated oligosaccharides that occur in surface carbohydrates that are common in certain cancers.…”
Section: Molecular Receptors and Sensorsmentioning
confidence: 99%
“…17 Recently, Hall and co-workers found that benzoxaborole groups showed a higher affinity than boronic acid toward saccharides at physiological pH as it has a physiologically suitable pK a of 7.2. 18,19 We have recently reported the successful preparation of benzoxaborole-containing polymers and demonstrated their specific interaction with glycolpolymers under various conditions. 20,21 In this study, we investigated selective sugar recognition of benzoxaborole-containing polymers using different monoand disaccharides.…”
mentioning
confidence: 99%